A Study of Agrivoltaics Peanut Production With Single-Axis Tracking Systems - Milena Chanes de Souza; Ricardo Nery de Castro; Benhur Azambuja Possato; Matthias B. Krause; Sol Hutson (AgriVoltaics Conference Proceedings)
This study investigates the application of single-axis solar tracking systems in peanut production, a crucial crop for global food security and economic sustainability. The experiment was conducted at the FIT Solar Laboratory in Sorocaba, Brazil, from May to September 2023. Peanut plants were cultivated under two conditions: an Agrivoltaic system with bifacial solar modules with a single axis tracking system, and in a conventional agricultural setup. Key findings indicate that peanut biomass yield under Agrivoltaic systems was 17.02% lower than in traditional agricultural systems, primarily due to shading effects inherent to the dual-use configuration. Despite this reduction, the morpho-physiological parameters of peanut plants, including plant height (31.2 ± 1.5 cm), stem diameter (5.3 ± 0.3 mm), stomatal conductivity (0.24 ± 0.02 mol/m²·s), and chlorophyll index (34.6 ± 2.1 SPAD units), remained stable under the Agrivoltaic system, demonstrating the adaptability of peanut plants to lower light conditions. Photosynthetically active radiation (PAR) measurements varied significantly depending on the position under the trackers, with values ranging from 150 to 1,200 µmol/m²·s, reflecting the heterogeneity of light distribution. The Agrivoltaic system achieved an energy production of 2,354.82 kWh/kWp, reflecting a minimal deviation of 4.36% compared to the PV-only control system, which recorded 2,462.26 kWh/kWp. The Energy Performance Index (EPI) for the Agrivoltaic system was calculated at 0.96, demonstrating its efficiency in converting available solar energy under real-world conditions. This performance aligns with industry standards, underscoring the efficiency of single axis tracking systems in balancing agricultural and energy outputs.